Themes in sentencing young adults charged with serious violent crime involving alcohol and other drugs - Lawler, Siobhan M. (The Australian and New Zealand journal of criminology, 2020)
The majority of young people in custody have alcohol and other drug problems and over 90% report past-year experiences of high-risk drinking and illicit drug use. Despite a strong link between drug use and violent offending, there is a dearth of information about how this relationship plays out in sentencing young adult offenders. This study examines themes in the sentencing of drug-using young adults facing court for serious violent crime and describes how judges discuss rehabilitation as a consideration for this high-risk group. This research contributes to the literature by bridging law and social science through a cross sectional analysis of n = 507 sentencing remarks from New South Wales higher courts. Substance use involvement was indicated in more than three-quarters (77%) of violent offence cases. Among young adults sentenced for violent crimes involving substance use (n = 51) robbery and homicide were the most common offences, and alcohol and methamphetamine were the most frequently involved substances. Two themes emerged around judges’ reasons for sentencing, one emphasising offender agency and choice and another more compassionate position acknowledging the influence of drug dependence on offending behaviour. Despite this divide, addressing substance use dependence was commonly seen as key for the successful rehabilitation of young people who commit violent crime involving alcohol and other drugs.